Adaptive Structuration Analysis in Innovation Communication of Indonesian National Standard in Micro, Small and Medium Enterprises - Pari, Farida; P Lubis, Djuara; Bintari P, Riko (Jurnal Penyuluhan, 2020)
Micro, small and medium enterprises (MSMEs) as one of the business sector which give significant contribution to national GDP have an average of more than 55% in the period 2008 to 2012 (BSN 2013), in addition, the role of food-based MSMEs is very important in providing adequate food availability for the community. Standardization is one of the strategies to increase competitiveness, especially in the free trade era. Standardization activities in the industry is proven by obtaining SNI certificates (Indonesian National Standards). This study aims to understand how the characteristics and evaluation of the nature of innovation towards MSME decisions to adopt SNI certification in the food sector. This quantitative research uses explanatory type method with an explanatory nature with associative nature because it wants to explain the influence between the variables tested. The results on evaluating the nature of innovation can be seen from the relative profit, the average respondent answers strongly agree on what they think of SNI or its products labelled SNI. Then on the level of complexity, respondents consider changes in infrastructure and adjustments to product standards. On marketing factors, respondents market their products through online media is 45,9% while marketing through offline media is 54%, one of which dominates them is through exhibitions or bazaars (15,3%). The conclude that there was no significant influence between the evaluation of the nature of innovation, namely the level of relative profitability, level of complexity and the level of observability with adoption of SNI certification. The factors that influence significantly SNI certification was adaptive structuration, they are rate of socialization and testimonial approach..